사회 참여 향상을 위한 발달장애 청소년의 의사소통 수준에 대한 양육자의 인식 및 요구 - 이명순(Myoung Soon Lee); 박현(Hyun Park) (언어치료연구, 2018)
목적: 본 연구는 발달장애 청소년의 사회참여 향상을 위하여 각 의사소통 영역의 난이도에 따른 부모의 의사소통 수준 인식과 의사소통 요구에 대한 정도를 파악하고 비교하였다. 방법: 본 연구를 위해 문헌고찰과 10년이상의 언어치료 경험이 있는 언어치료사 또는 언어치료 전공 학과 교수 등 5명의 검정을 통하여 설문지를 구성하였고 대학 내 언어치료 센터 이용 부모님 5명을 대상으로 예비 조사를 실시하였다. 설문지의 구성은 대상자와 자녀에 대한 일반적인 사항과 이해하기, 표현하기, 읽기, 쓰기 등 4가지 언어 양식의 현재 수준 인식과요구도, 그리고 사회적 의사소통 항목에 대한 요구도 등 5개의 영역으로 이루어졌다. 본 조사는 2017년 10월5일부터 10월 20일 까지 모바일을 통한 응답이 이루어졌고, 총 119 부를 회수하여 101부를 분석하였다. 자료들은 SPSS 18.0 프로그램을 사용하여 기초사항, 이해하기, 표현하기, 읽기, 쓰기, 사회적 의사소통에 대한빈도 분석과 자녀 연령, 발견 시기, 장애 등급, 장애 유형, 언어치료 기간에 따른 집단 간 차이를 알아보고자기술적 통계를 제시하였다. 결과: 본 연구의 결과는 다음과 같다. 첫째, 기초사항에 대한 빈도 분석 결과 발달장애 청소년의 언어치료 기간은 10년이 이상이 39.6%로 가장 높고 향후 치료를 지속하거나 받고 싶다는 의지가 55.4%로 매우 높았다. 둘째, 발달장애 청소년의 의사소통 수준에 대한 부모 인식은 이해하기의 ‘일상어휘 이해’ 긍정적인 답변이 높았고 단계가 높을수록 부정적인 반응이 높았고, 영역 중에서는 쓰기 영역에서 부정적 반응이 높았다. 결론: 결론적으로 발달장애 청소년의 언어치료는 사회참여를 목적으로 의사소통적 차원에서 이루어져야 하며 부모의 의사소통 치료 요구도를 반영하여 효율적인 치료가 이루어지기 위해서는 언어치료사의 사회적 의사소통 하위 요소에 대한 분석과 개발이 필요하다. Purpose: In this study, the awareness and the demands of parents on the communication level to improve the social participation of youth with developmental disabilities were identified and compared. Method: A questionnaire composed of five domains such as general matters of the subject and children; current awareness level; demand for the four language forms (understanding, expressing, reading and writing); and the demand for the social communication items was devised. Frequency analysis was performed for basic matters such as understanding, expressing, reading, writing and social communication by using SPSS 18.0 and descriptive statistics. Results: The results of this study are as follows. First, in the frequency analysis, results on the basic matters during the speech therapy period were the highest at age 10 and above when the will to continue or receive therapy in future was the highest (55.4%). Second, in the parents' awareness on the communication level of the youth with developmental disabilities, the positive response of the understanding of daily life vocabulary was high; in addition, the higher the stage, the higher the negative response. Out of the domains, the negative response was high in the domain of writing. Conclusion: In conclusion, speech therapy for youth with developmental disabilities should be made in the dimension of communication for the purpose of social participation and for efficient therapy reflecting the demand of the parents for communication therapy. The sub-factors of social communication require analysis and development by speech therapists. KCI Citation Count: 0